Household financial burden associated with out-of-pocket payments for healthcare in Iran: insights from a cross-sectional survey - Satar Rezaei; Maryam Karimi; Shahin Soltani; Eshagh Barfar; Mohammad Ali Mohammadi Gharehghani; Abbas Badakhshan; Nasim Badiee; Mohsen Pakdaman; Heather Brown (BMC, 2024)
Abstract Background One of the key functions and ultimate goals of health systems is to provide financial protection for individuals when using health services. This study sought to evaluate the level of financial protection and its inequality among individuals covered by the Social Security Organization (SSO) health insurance between September and December 2023 in Iran. Methods We collected data on 1691 households in five provinces using multistage sampling to examine the prevalence of catastrophic healthcare expenditure (CHE) at four different thresholds (10%, 20%, 30%, and 40%) of the household's capacity to pay (CTP). Additionally, we explored the prevalence of impoverishment due to health costs and assessed socioeconomic-related inequality in OOP payments for healthcare using the concentration index and concentration curve. To measure equity in out-of-pocket (OOP) payments for healthcare, we utilized the Kakwani progressivity index (KPI). Furthermore, we employed multiple logistic regression to identify the main factors contributing to households experiencing CHE. Findings : The study revealed that households in our sample allocated approximately 11% of their budgets to healthcare services. The prevalence of CHE at the thresholds of 10%, 20%, 30%, and 40% was found to be 47.1%, 30.1%, 20.1%, and 15.7%, respectively. Additionally, we observed that about 7.9% of the households experienced impoverishment due to health costs. Multiple logistic regression analysis indicated that the age of the head of the household, place of residence, socioeconomic status, utilization of dental services, utilization of medicine, and province of residence were the main factors influencing CHE. Furthermore, the study demonstrated that while wealthy households spend more money on healthcare, poorer households spend a larger proportion of their total income to healthcare costs. The KPI showed that households with lower total expenditures had higher OOP payments relative to their CTP. Conclusion The study findings underscore the need for targeted interventions to improve financial protection in healthcare and mitigate inequalities among individuals covered by SSO. It is recommended that these interventions prioritize the expansion of coverage for dental services and medication expenses, particularly for lower socioeconomic status household.